Persepsi Mahasiswa Program Studi Akuntansi Terhadap Pengetahuan Teknologi Informasi Dan Komunikasi Yang Harus Dikuasai Seorang Akuntan (Studi Kasus Pada Mahasiswa Universitas Muhammadiyah Riau) - Ressy Agmallia; Muharini Ulya Sari; Annisa Rahima Ramadhani; Mutia Afrianti; Siti Rodiah (Jurnal Ilmiah Ekonomi Terpadu (Jimetera), 2022)
This study aims to examine the differences in perceptions of accounting students based on gender and the cumulative predicate index on technology knowledge for accountants. The data in this study were collected using a questionnaire sent to 100 male and female students from a population of 737 students in the 2018 2019 and 2020 accounting study programs. The data used is raw data (primary) obtained through a survey by distributing questionnaires. . The data analysis technique used in this research is normality test, independent sample and One Way Anova. Results of this study indicate that there is no difference in the perception of students in the accounting study program based on gender and the cumulative predicate index on information and communication technology knowledge that accountants must master.Keywords: Gender, Cumulative Predicate Index, Knowledge of Information and Communication Technology